Kabarangay Ginebra fans and their emotions during live games - Manicad, Macario III B. 1993- (2014)
"Philippines has always been branded as a 'basketball crazy nation'. On May 2013, Philippine Basketball Association (PBA) Commissioner Attorney Chito Salud expressed gratefulness for the 'renewed fan interest', that the PBA is on the upswing because the fans are taking a second look at what the league offers, which is top-notch sports competition and entertainment. In fact, there is an increase in the gross gate receipt in the last three years from Php 90 million in 2011, Php 114 million in 2012 and over 200 million in 2013. Game Three of the 2013 Commissioner's Cup Finale between Ginebra and Alaska also set the all-time one-game record crowd of 23,436. In light of the observation, as a basketball fan and a follower of PBA, I conducted an ethnographic, participant observation study to understand the PBA fans' emotions in a live basketball game based on a conative component and having Barangay Ginebra fans, arguably one of the largest crowd drawer in the PBA and the most celebrated fandom in the history of Philippine basketball, as focal point for data gathering and analysis. Integrating concepts from theory on fandom and emotions, the researcher aims to determine the context of the Ginebra fandom, observe and record the expressive behaviors of Ginebra fans, and explore the 'collectiveness' of the Ginebra fandom."